Researching elite athletes' pure experience and consciousness - Matsuyama, N. (International Journal of Sport & Health Science, 2018)
This study sheds light on researchers` understanding of athletes` pure experience and consciousness with the aim of advancing the research field of pure experience and consciousness to make sport coaching more efficient in enabling high performance. To discuss questions regarding researchers` understanding of athletes` pure experience and consciousness, this study proposes a philosophical idea to interpret athletes` pure experience and consciousness in performance using an ideographic approach with interviews based on phenomenology. In this approach, this research focuses on one elite high jumper who is a winner of the Japan National Championships to explore his pure experience and consciousness that have enabled his high performance.